Contributions to Reverse Logistics with Game theoretic Applications - Wu, Sandy Huyu (My University, 2012)
The last two decades witnessed an increasing emphasis on reverse logistics (RL). Our thesis attempts to investigate two research problems in RL and explore game theoretic applications in this field.
In Chapter 1, we introduce SCM, RL, relevant game theoretic applications, and the organizational structure of this thesis.
In Chapter 2, we address a newsvendor problem with resalable returns. We develop a basic model with order quantity as the single decision variable and conduct concavity analysis. We also develop a general model in which the retailer determines both order quantity and two inter-period inventory thresholds. We use simulation to investigate the timing effect of both customer demands and returns on the retailer's decision making.
In Chapter 3, we explore the application of game theoretic models with incomplete information in inventory management. Games with incomplete information may provide a more realistic modeling framework. We hope this exposition be helpful to researchers interested in applying game theoretic models and computing equilibriums in their specific problems in SCM and RL.
In Chapter 4 we consider a remanufacturing competition problem between an original equipment manufacturer (OEM) and a pure remanufacturer (REM) with the OEM's incomplete information on the REM's unit cost. We apply the type-III model in Chapter 3 for formulation and derive the closed-form Bayesian Nash equilibrium. We use sensitivity analysis to investigate the effect of such incomplete information on both competitors' decision making.
We summarize in Chapter 5 and provide a general direction for future research on game theoretic applications in RL.
Keywords: Reverse logistics; inventory management with resalable returns; competition in remanufacturing; game theory; game theoretic applications with incomplete information; Management Sciences and Quantitative Methods; Management Sciences and Quantitative Methods